Identifying Hedge Fund Skill by Using Peer Cohorts. Issue 2 (3rd April 2021) - Forsberg, David; Gallagher, David R.; Warren, Geoffrey J.
Abstract : We propose a cohort model that evaluates hedge funds against peer groups executing similar investment strategies formed by using return correlations. Our method improves the identification of skilled managers, as evidenced by a strong ability to explain hedge fund returns out-of-sample, with cohort alpha being more persistent than alpha based on the widely accepted seven-factor model. A hedge fund-of-funds analysis found significant performance enhancement from exposure to the best funds within each cohort. The cohort approach can be used to enhance the construction of hedge fund-of-funds portfolios by isolating strategy groupings as well as the best managers within each group. Abstract : Disclosures: The authors have no conflicts of interest to declare. The content of this article reflects the views of the authors and not necessarily the views of BlueCove Limited. Editor's Note: Submitted 2 September 2020. Accepted 6 January 2021 by Moshe Arye Milevsky This article was externally reviewed using our double-blind peer-review process. When the article was accepted for publication, the authors thanked the reviewers in their acknowledgments. Nicole M. Boyson and one anonymous reviewer were the reviewers for this article.